Linking Public Investment Programs and SPAHD Macro Models : Methodology and Application to Aid Requirements - Agénor, Pierre-Richard; Bayraktar, Nihal; Pinto Moreira, Emmanuel (World Bank, Washington, DC, 2012)
The authors propose a "bottom up" approach to link public investment programs with a class of macro models recently developed to quantify Strategy Papers for Human Development (SPAHD) in low-income countries. The methodology involves establishing constant-price projections of investment outlays (disaggregated into infrastructure, education, and health), spending on maintenance and other goods and services, salaries, and user charges. These estimates are incorporated in a SPAHD macro framework to calculate, under alternative scenarios, domestic financing, foreign borrowing, and aid requirements. The authors also evaluate the impact on growth and indicators associated with the Millennium Development Goals. They use illustrative applications, based on a SPAHD model for Niger, to highlight the link between tax reform and aid requirements.